2017
DOI: 10.1159/000452725
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte and Acid-Base Disorders in Chronic Kidney Disease and End-Stage Kidney Failure

Abstract: The kidneys play a pivotal role in the regulation of electrolyte and acid-base balance. With progressive loss of kidney function, derangements in electrolytes and acid-base inevitably occur and contribute to poor patient outcomes. As chronic kidney disease (CKD) has become a worldwide epidemic, medical providers are increasingly confronted with such problems. Adequate diagnosis and treatment will minimize complications and can potentially be lifesaving. In this review, we discuss the current understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 127 publications
(144 reference statements)
6
109
0
8
Order By: Relevance
“…In dialysis patients requiring high protein intake, risk for hyperphosphatemia can be substantial and should be carefully monitored and when appropriate, phosphate binders should be promptly instituted [143]. A recent prospective study by Rhee et al of a cohort ( n = 110) of hypoalbuminemic hemodialysis patients showed beneficial effects of increasing serum albumin (≥0.2 mg/dL) and maintaining serum phosphorous levels within a target range (3.5 to <5.5 mg/dL) by providing high-protein meals during hemodialysis combined with lanthanum carbonate administration [144].…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…In dialysis patients requiring high protein intake, risk for hyperphosphatemia can be substantial and should be carefully monitored and when appropriate, phosphate binders should be promptly instituted [143]. A recent prospective study by Rhee et al of a cohort ( n = 110) of hypoalbuminemic hemodialysis patients showed beneficial effects of increasing serum albumin (≥0.2 mg/dL) and maintaining serum phosphorous levels within a target range (3.5 to <5.5 mg/dL) by providing high-protein meals during hemodialysis combined with lanthanum carbonate administration [144].…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…We have previously shown that SERCA2a KO mice have a reduced LV inner diastolic diameter (LVID;d), subsequently necessitating a lower LV inner systolic diameter (LVID;s) to maintain stroke volume before acute decompensation [14]. This phenotype was seen in both HF groups, with no additional effect of TLR9 deficiency on LV dimensions (Figures 1(b) and 1(c)) nor on left atrium size (Figure 1(d)).…”
Section: Resultsmentioning
confidence: 72%
“…The sarcoplasmic/endoplasmic reticulum Ca 2+ ATPase (SERCA) is the main cytosolic Ca 2+ removal transporter and regulates cardiac relaxation [12]. We have previously shown that mice with cardiomyocyte-specific deletion of SERCA2a (SERCA2a KO) develop diastolic HF as compared with wild-type (WT) mice [13, 14]. Using this HF model, we demonstrated that chronic exposure to systemic TLR9 stimulations aggravated diastolic HF [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic kidney disease (CKD) and end-stage kidney failure (ESRD) are prone to develop metabolic derangements, especially acid-base and electrolyte imbalances [1]. Their presence imparts morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%